(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Pre-eclampsia is an idiopathic disorder of pregnancy characterized by proteinuric hypertention and still one of the important causes of maternal and fetal mortality.The identification of its predisposing factors before and during early stage of pregnancy will help in reducing the mortality. Objective:The objective of the present study is to determine the risk factors for pre-eclampsia among pregnant women in a tertiary level hospital. Methods: This study was conducted in the Department of Obstetrics and Gynaecology of a tertiary care hospital in Chittagong, Bangladesh, from January to June 2015.A total number of 50 pregnant women with pre-eclampsia who admitted in this hospital were selected as study group.This was hospital based descriptive study. Results: Most of the partcipants were within 21-30 years of age group and mean age 24.06 ± 3.71.The factors that were found to be significant predictors of risk for development of PE were primigravida, low socioeconomic condition,family history of PE & hypertension, past history of PE and hypertention, past history of diabetes mellitus was also associated with development of PE. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 29-32